Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1371/journal.pone.0061207
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pre-Existing Disturbances in the Effect of Marine Reserves on Coastal Ecosystems: A Modelling Approach

Abstract: We have used an end-to-end ecosystem model to explore responses over 30 years to coastal no-take reserves covering up to 6% of the fifty thousand square kilometres of continental shelf and slope off the coast of New South Wales (Australia). The model is based on the Atlantis framework, which includes a deterministic, spatially resolved three-dimensional biophysical model that tracks nutrient flows through key biological groups, as well as extraction by a range of fisheries. The model results support previous e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
(68 reference statements)
0
10
0
3
Order By: Relevance
“…Similarly, if MPAs are too large, economic benefits may be diminished. Unintended effects such as displaced effort or trophic cascades have been suggested by many modeling studies of MPAs, for instance by Walters et al (1999), and more recently by Savina et al (2013) who found negative impacts on prey fish when MPAs promoted shark recovery in a study of New South Wales, Australia. Here we test the assertion by Fulton et al (2015) that MPAs perform best in terms of specific objectives related to species recovery, but that they can lead to tradeoffs across species and ecological objectives such as biodiversity and economic equity.…”
Section: Implementation Of Marine Protected Areasmentioning
confidence: 96%
“…Similarly, if MPAs are too large, economic benefits may be diminished. Unintended effects such as displaced effort or trophic cascades have been suggested by many modeling studies of MPAs, for instance by Walters et al (1999), and more recently by Savina et al (2013) who found negative impacts on prey fish when MPAs promoted shark recovery in a study of New South Wales, Australia. Here we test the assertion by Fulton et al (2015) that MPAs perform best in terms of specific objectives related to species recovery, but that they can lead to tradeoffs across species and ecological objectives such as biodiversity and economic equity.…”
Section: Implementation Of Marine Protected Areasmentioning
confidence: 96%
“…Harvest (or bycatch) of both predators and prey, such that harvest release can outweigh predation increase in prey T: (Baskett 2006, Kellner et al 2010, Micheli et al 2004a, Savina et al 2013, Takashina et al 2012) E: (Mumby et al 2006, Shears et al 2012 Weakened…”
Section: Weakenedmentioning
confidence: 99%
“…The sophistication of EwE with Ecospace and Atlantis allows these modeling approaches to tackle a wide number of EBFM issues, including MPA effectiveness (e.g. Salomon et al 2002, Martell et al 2005, Savina et al 2013, Olsen et al 2018, the consequences of bycatch reduction measures (e.g. Fulton et al 2007, Walters et al 2010, Morzaria-Luna et al 2012, 2013, and management strategy evaluations integrating ecosystem considerations (e.g.…”
Section: Introductionmentioning
confidence: 99%